Gender representations in politics of belonging: An analysis of Swiss immigration regulation from the 19th century until today. (August 2017) - Fischer, Carolin; Dahinden, Janine
The literature increasingly recognises the importance of gender in defining the boundaries between national societies and migrants. But little is still known about the history and changes of mechanisms that shape the role of gender as category of difference. Based on a critical case study of Switzerland, this article examines how gender is implicated in the politics of migrant admission and incorporation and underlying notions of 'the other'. Drawing on theories of boundary work, we show that gendered representations of migrants are mobilised by different actors to advance their claims and calls for certain forms of immigration control and migrant integration. Since the late 19th century, gendered representations of Swiss nationals and migrant others shift from classical gender ideas to culturalised post-colonial interpretations of gender roles and, most recently, to normative ideas of gender equality. As part of these changes, migrant women moved from the periphery to the core of public and political attention. Concomitantly, categories of difference shift from the intersection of gender and social class to an intersection of gender, culture and ethnicity. Local particularities of Switzerland – the idea of 'overforeignisation' and the system of direct democracy – play a significant role in shaping categories. But Switzerland's embeddedness in transnational fields emerges as equally important. The article expands on recent research and illuminates how changing dynamics of categorisation and othering facilitate the construction of nations and national identities in a transnationalised world.